Crop Biomass, Soil Carbon, and Nitrous Oxide as Affected by Management and Climate: A DayCent Application in Brazil. Issue 4 (17th August 2017) - Weiler, Douglas Adams; Tornquist, Carlos Gustavo; Parton, William; dos Santos, Henrique Pereira; Santi, Anderson; Bayer, Cimelio
Abstract : Core Ideas: DayCent was calibrated and validated using 30‐yr‐old experiments in southern Brazil. We simulated current and alternative management practices to 2100 using IPCC scenarios A2 and B1. Model predicted crop biomass increases from 5 to 65% depending on cropping system and scenario. Climate change would lead to larger relative increases in soil N2 O emissions from no‐tillage (27% in B1 to 41% in A2). N2 O fluxes under no till would still be 25% lower than under tillage. A current national research priority in Brazil is the assessment of potential climate change impacts in agriculture. In this study, the DayCent model was used to predict changes in crop biomass, soil C stocks, and N2 O fluxes of a major agricultural area in Brazil. The model was calibrated and validated using datasets from 30‐yr‐old experiments. Simulations of current and alternative management practices to 2100 using IPCC climate scenarios A2 and B1 were conducted. Predicted crop biomass increases ranged from 5% (sorghum [B1]) to 65% (soybean [A2]). DayCent simulated higher soil organic carbon stocks in the wheat–soybean system (VAL1) than in the wheat–soybean–vetch–sorghum system (VAL2) in both climate scenarios. Soil organic carbon accumulation by 2100 (±16 Mg C ha ‐1 above current 46 Mg C ha ‐1 ) was forecast in cropping systems with pastures ( Cynodon sp.), regardless of the climate scenario. Daily N2 O fluxes were underestimated by ±41% (0.85 g N–N2 O ha ‐1 d ‐1 ) in VAL1 and overestimated by 17.5% (0.28 g N–N2 O ha ‐1 d ‐1 ) in VAL2. Cumulative N2 O fluxes produced mixed results, which were 29% lower than observed in VAL1 and 5% higher in VAL2 but within the range of values reported in other greenhouse gas studies in southern Brazil. Simulations of N2 O fluxes to 2100 with IPCC climate change scenarios B1 and A2 in southern Brazilian indicated higher annual fluxes across the alternative treatments tested in comparison to current fluxes. According to model predictions, climate change would lead to larger relative increases in N2 O emissions from no‐tillage (27% in B1 to 41% in A2), but these enhanced fluxes would still be lower than those from tillage by approximately 25%.